Contribution to the knowledge of Turkish stoneflies with annotated catalogue (Insecta: Plecoptera) - Darilmaz, Mustafa Cemal; Salur, Ali̇; Murányi, Dávid; Vinçon, Gilles (Zootaxa, 2016)
The stoneflies of Turkey are reviewed providing all known distributions and including new records. Additionally, ecological and biogeographical notes are given. The genus Taeniopteryx Pictet 1841 is reported from Turkey for the first time and 12 species new for the Turkish fauna: Leuctra joosti Braasch 1970, L. kopetdaghi Zhiltzova 1972, Protonemura rauschi Theischinger 1975, P. strandschaensis Braasch & Joost 1972, Nemoura asceta Murányi 2007, N. cambrica Stephens 1836, N. uncinata Despax 1934, Taeniopteryx caucasica Zhiltzova 1981, Brachyptera risi (Morton 1896), Pontoperla katherinae (Balinsky 1950), Siphonoperla neglecta (Rostock 1881), and Bulgaroperla mirabilis nigrita Zwick 1978.          Protonemura bithynica Aubert 1964 and Nemoura turcica Zwick 1972 are recognized as full species. The previously unknown female of Leuctra marilouae Vinçon & Sivec 2001 is described. The type locality is also given for each species located in Turkey.          The distributions of several rare endemic species are augmented by additional new records (Leuctra aculeata Zwick 1982, L. brachyptera Kazancı 1985, L. karcali Vinçon & Sivec 2001, L. kurui Kazancı 1983, L. marilouae Vinçon & Sivec 2001, L. sipahilerae Vinçon & Sivec 2001, L. theischingeri Vinçon & Sivec 2001, Protonemura bacurianica bacurianica Zhiltzova 1957, P. oreas Martynov 1928, P. spinulata Martynov 1928 (first confirmed records from Anatolia), P. triangulata Martynov 1928, Nemoura dromokeryx Theischinger 1976, N. martynovia Claassen 1936, and Brachyptera berkii Kazancı 2001.          Several species previously reported only from females are excluded from the Turkish fauna: Leuctra minuta minuta Zhiltzova 1960, L. svanetica Zhiltzova 1960, P. dilatata Martynov 1928. Other species are also excluded from the Turkish fauna: L. fusca fusca (Linnaeus 1758), N. carpathica Illies 1963, Siphonoperla burmeisteri (Pictet 1841), and S. libanica Alouf, 1992.          According to literature and our new faunistic data, 117 stonefly taxa representing 7 families and 24 genera are known from Turkey. Among them, 44 are endemic species from Anatolia.